Approximation of periodic functions by interpolation polynomials in L_1 - Motorny, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
Asymptotically precise estimates are obtained for the deviation, in the L_1-norm, of interpolation polynomials with equally-spaced nodes from certain classes of functions.